Orlando e a tradução da personagem para as telas - Barros, Francisco Rafael Silva (2012)
The following study analyses the translation of the novel/biography Orlando (1928), by Virginia Woolf, to its homonymous film adaptation in 1993, directed by Sally Potter. Orlando tells the story of an English nobleman who owns the gift of literary writing and lives for more than three hundred years, changing his sex, from male to female. The focus of our research is the translation of the main character, Orlando, from novel to film: we outlined some aspects of his/her personality to understand him/her actions throughout the novel/biography, and also considered some external aspects that complement or are part of his/her construction. Then, we submit the film character to the same process, to compare both. In order to do so, we started from a prior historical contextualization of the objects and their contexts of production. Our research is based on Itamar Even-Zohar’s polysystem theory (1978), the concept of translation as rewriting, by Andre Lefevere (2007), Antonio Candido’s study of the fictional character (2007), and Jacques Aumont’s studies about the aesthetics of cinema (1995). We do not intend to evaluate any of the objects (novel and movie), or to say that one is better than another. However, we aim to demonstrate what was the contribution of the character of the novel/biography to the construction of the film character, and to what extent the film character contributes and influences to the new readers of Woolf’s book. Primarily, we are aware that the construction of the character in the novel/biography is linked to two fundamental points: Vita Sackville-West, to whom the novel is dedicated, and the desire of freedom (intellectual and financial) to the writer, a relevant theme in Woolf’s speeches and writings of that decade. Sally Potter deals with her character’s immortality and freedom desire in a different way: her focus turns into implications of social and post-colonial issues, turning Orlando from an initial British identity to a more universal one. This research is sponsored by Fundação Cearense de Apoio ao Desenvolvimento Científico e Tecnológico – FUNCAP.